Business - Pride, William M., 1942-; Hughes, Robert James, 1946-; Kapoor, Jack R., 1937- (Boston : Houghton Mifflin Co., 1988)
"The second edition of Business covers new topics, presents expanded coverage of important issues, focuses on small as well as large business, provides thorough career information, and contains numerous pedagogical aids." The comprehensive ancillary package includes Microstudy Plus, a new self-help computer-aided instructional diskette, and Business video file, a free series of twenty-four videos one for each chapter and the Appendix.
Authors of the first ed.: Robert J. Hughes and Jack R. Kapoor.
Includes indexes.
Bibliography: p. [11]-[14] (3rd group)
English text.
Keywords: Business enterprises -- United States; Industrial management -- United States; Business; Management